Physiological Responses and Bout Analysis in Elite Kickboxers During International K1 Competitions - Rydzik, Łukasz; Maciejczyk, Marcin; Czarny, Wojciech; Kędra, Andzej; Ambroży, Tadeusz (Frontiers in Physiology, 2021)
Background: Kickboxing is a combat sport with a variation of types of rivalry. Fighting accord-ing to K1 formula rules is one of the most interesting and quickly developing type of kickbox-ing. According to K1 formula rules it is possible to use a variety of techniques and punches with a great force. A physiological response during a real sport fight allows to assess the load of the organism during a bout and making adjustments of fitness training to better fit the requirements of a fight. The objective of the study was to observe the physiological response during a real sports fight as well as technical and tactical analysis of the fight conducted according to K1 for-mula rules. Methods: The study was conducted during two cycles of international kickboxing league according to K1 formula rules in a group of 15 elite fighters. The indicators of technical and tactical training were evaluated (activeness, effectiveness and efficiency of the attack) as well as level of acidification, heart rate, and restitution rate during a real sport fight. Based on physi-ological analysis the intervals pointing the recommended training loads were proposed. Results: Efficiency of the attack was on average 59.3±2.7, its effectiveness - 50.3±10.01, and its activeness - 112.3±29. The mean intensity of work was 96.8±2,9% of maximal heart rate and lactate concen-tration was 14.6±1.9 mmol/L. Conclusions: A kickboxing fight was a strong physiological stress for the participants. Reported heart rate and lactate concentration show that the intensity of work was close to its maximal value and anaerobic metabolism played an important role during a fight. Based on the study practical training recommendations were made suggesting keeping the intensity of the training at 95% HRmax level.